The survival of the bark canoe - McPhee, John A.; Adney, Edwin Tappan, 1868-1950. (New York : Farrar, Straus, Giroux, 1975)
An account of a 150-mile canoe trip through Maine woods and over Maine waters, together with the evolution and history of the bark canoe that played a major role in opening up the wilderness.
"Story of the building of birch-bark canoes and of a 150- mile trip through the Maine woods"--back cover (1990 paperback printing).
"A portfolio of the sketches and models of Edwin Tappan Adney (1868-1950)": p. [115-145]
Keywords: Vaillancourt, Henri; Canoes and canoeing -- Maine